Pengembangan Strategi Pembelajaran Pengkonkritan Materi Abstrak PAI Anak Usia Dini di RA Perwanida 3 Palembang - Istianatun Nafi'ah (Bahasa Indonesia, Bahasa English, 2019)
Early childhood who are in the preoperational stage have not been able to think logically and abstractly, but Islamic religious subjects that must be instilled in children from an early age especially the aspects of aqidah are included in the abstract material category, thus learning strategies are needed that can make it easier for students to understand abstract material the. This study aims to produce a learning strategy for the abstracting of PAI abstract material for early childhood in RA Perwanida 3 Palembang, knowing the results of expert validation, and knowing the effectiveness of the learning strategy for the abstracting of PAI abstract material for early childhood in RA Perwanida 3 Palembang. This research is research and development. The research and development stages are requirements analysis, planning, product design development, product validation and revision, trials and revisions, final product. The results of the study are: 1) the product developed in the form of a draft learning strategy design, 2) the learning strategy is assessed and validated based on the aspects of the suitability of the media and methods to the material, student characteristics, time allocation and infrastructure, the results of the assessment of learning strategies obtain an average score 4.62 with the category "very appropriate", 3) the average test score of 13 students before using the developed learning strategy is 6.3885 while after using the developed learning strategy the average student score is 7.3462. While the paired samples test obtained 0.000 significance less than the 0.05 significance level. Based on the results of the assessment, the learning strategy of abstracting PAI material in early childhood in RA Perwanida 3 Palembang is effective and feasible to use.